Communication Medium Used by Clients and Health Professionals in Accessing and Providing Healthcare in Low Resource Setting: A Descriptive Cross-Sectional Study - Mathias Dongyele; Daniel Ansong; Francis Adjei Osei; Evans Xorse Amuzu; Nicholas Karikari Mensah; Alfred Kwame Owusu; Bright Atta Dankwa; Samuel Frimpong Odoom; Joseph Bonney; Duncan Adjei; Anne Amusu; Emmanuel Kofi Akowuah; et al. (Hindawi Limited, 2021)
Background. There exist continuing challenges with communication medium used during health service provision. These challenges relate to clients and health institution, intra- and interhealth institution communications. This study reviewed the existing healthcare communication medium from the perspectives of clients and health professionals at a tertiary hospital in Ghana. Methods. Cross-sectional design was employed with a multilevel sampling method to select a total of 650 participants consisting of 303 clients, 303 health workers, and 44 hospital directorate managers for the study. A structured survey questionnaire was used to collect data from respondents. Results. Close to ninety percent (89.8%) of staff resort to direct means (face-to-face medium) to communicate among each other. Majority (64.4%) of them also communicated with management through meetings sections. Nearly all healthcare providers (97.4%) communicated with clients through direct means (face-to-face medium). Almost all forms of communication between the hospital management members and the general public were done through letters and official memos. Conclusions. The study revealed blended forms of communication media used by health providers and health service consumers. These differences in medium of communication could amount to possible difficulties such as lack of information and truncation of information flow. Developing a systematic way of information flow using a common information platform will improve access to health services.